Curaca etnia Shapra - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó el rostro del curaca de la etnia Shapra con su corona de plumas, aretes de alas de escarabajos y collares de semillas.
ENGLISH: The face of the curaca of the Shapra ethnic group was observed with its feather crown, beetle wing earrings and seed necklaces.

SPANISH: Se observó el rostro del curaca de la etnia Shapra con su corona de plumas, aretes de alas de escarabajos y collares de semillas.
ENGLISH: The face of the curaca of the Shapra ethnic group was observed with its feather crown, beetle wing earrings and seed necklaces.
Shapra ethnic cacique
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Curacas and Authorities|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Curacas y Autoridades.|~|/ Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Curacas and Authorities.